Book Review: A Social History of the English Countryside - Paul Theobald (Journal of Research in Rural Education, 1994)
Isuppose the question is obvious: why review this book in a journal that focuses predominantly on rural education in the United States? The not-so-obvious answer is that it provides a "big picture" perspective regarding the health and well-being of rural communities and, by extension, rural schools. It also supplies intellectual leverage over a few lingering commonalties of small rural communities that have troubled education-minded rural reformers , throughout this century. Last, and probably most significant, the book pushes the reader to the realization that the near-century long trend of rural decline in this country is not the inevitable result of some law of nature, but rather the predictable result of shifts related to the locus of political and economic power.